How Role Overload Affects Physical and Psychological Health of Low-ranking Government Employees at Different Ages: The Mediating Role of Burnout - Qing Huang; Yidan Wang; Ke Yuan; Huaxing Liu (Elsevier, 2022)
Background: The public now imposes higher demands on the government than in the past, which has created the role overload faced by low-ranking government employees in China. This research investigates the relationship between role overload and health among low-ranking government employees and explores the mediating effects of burnout. Methods: It draws on a survey of 2064 low-ranking government employees by probability proportionate to size sampling in China's Shandong Province. Structural equation modeling (SEM) methods are used to analyze the data. Results: Both role overload and burnout were found to have negative effects on low-ranking government employees' health; however, the associations varied among the three age groups (less than 36, between 36 and 45, and over 45). Those over 45 reported the highest level of both physical and psychological health, while the youngest age group (less than 36) reported the lowest level of health. Role overload has a direct influence on health among government employees over 45 but not among those below 45. Burnout's mediating effects between role overload and health are significant among all age groups, but most significant among the youngest civil servants below 36. Conclusions: The findings evidenced that both role overload and burnout affect low-ranking government employees' self-reported physical and psychological health. In addition, the effect of age differences in coping with role stressors and burnout should be considered.